GROUNDWATER QUALITY ASSESSMENT FOR RESIDENTIAL AND IRRIGATION PURPOSES: A CASE STUDY OF FUTUK AND ITS ENVIRONS, NORTHERN BENUE TROUGH, NORTHEAST NIGERIA - Aliyu, Mustapha; Haruna, Ahmed Isah; Maigari, Abubakar Sadiq; Mohammad, Adamu Usman; Abdulkarim, Said; Lawal, Abdullatif; Umar, Umar Sambo; Nabage, Nuru Abdullahi; Dokoro, Mus’ab Adamu (FUDMA JOURNAL OF SCIENCES, 2024)
This research assesses the suitability of groundwater quality in the region for residential and agricultural use. To evaluate the water quality for domestic purposes, 15 samples of groundwater were taken and tested for various physicochemical parameters including pH, electrical conductivity (EC), total dissolved solids (TDS), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), sulfate (SO4), chloride (Cl), bicarbonate (HCO3), carbonate (CO3), and nitrate (NO3). The quality of irrigation water was evaluated using several parameters: permeability index (PI), sodium absorption ratio (SAR), total hardness (TH), residual sodium carbonate (RSC), and water quality index (WQI). Piper diagrams, Gibbs diagrams, and the chloro-alkaline index were used to determine groundwater facie classification and ion exchange mechanisms. When compared to the WHO 2011 standard, the physiochemical parameters are within the appropriate limits, with the exception of EC and NO3, which revealed excessive values in some samples. All of the measured parameters are suitable for irrigation activities. According to the Kelly index, there is just one sample that is inappropriate for irrigation. The predominant groundwater type in the area is calcium chloride, with sodium chloride constituting the second most common groundwater facies. The hydrochemical mechanism that regulates the local groundwater chemistry is reverse ion exchange. This indicates a positive index, resulting from the exchange of sodium (Na) and potassium (K) in the groundwater with calcium (Ca) and magnesium (Mg) in the aquifer components.